Homophily and Organizational Identification towards Organizational Commitment and Organizational Justice among Male and Female Office Workers in Iligan City - ESCALONA, ODESSA MAY D.; T. CANONO, ANNA PATRICIA; DEMIAR, DIANA ROSE A.; OMONDANG, MIKO NECO B. (Universitas Muhammadiyah Yogyakarta, 2016)
The study of identification within the organizational setting has highlighted various factors that may contribute significant changes, either positively or negatively, to the commitment and perception of fairness of employees. As workers, their jobs and relationship with their organization are also influenced by how they perceive people around them in terms of attitude and background. In connection, this study explored on the homophily and organizational identification towards the organizational commitment and organizational justice among male and female office workers in Iligan City. The respondents are male (n = 35) and female (n = 35) office workers coming from selected companies and institutions located in Iligan City. Based on the results and findings, there is a significant relationship between homophily and organizational identification; and organizational identification and organizational commitment among male office workers while there is a significant relationship between organizational identification and organizational justice among female office workers. Finally, there is a significant interaction between invested self-concept to organizational commitment of male office workers in Iligan City while there are significant interactions between background homophily to organizational justice; management connection to organizational justice; and coworker connection to organizational justice of female office workers in Iligan City.